Recep Tayyip Erdogan and the Istanbul Greater Municipal Eletions in 1994 (Journal of the College of Basic Education, 2022)
The study of political figures is one of the studies that highlight the role of individuals in understanding and interpreting many historical events. The contemporary history of Turkey witnessed the emergence of many of them, and each of them had an influential role in its events by virtue of their work, responsibilities, and positions, and among these figures the personality of Recep Tayyip Erdogan stands out. Study subject.The importance of the subject of the message lies in the fact that Recep Tayyip Erdogan is one of the important personalities who had a prominent role on the political level in the contemporary history of Turkey, as he is considered the maker of modern Turkey’s renaissance.There is no doubt that the study of prominent political figures who influenced the events requires accuracy and patience from the researcher in analyzing the sources that I wrote about him, some of them shed light on the positives of this personality and others focus on its negatives only, as well as those who try to obscure the facts, intentionally or unintentionally. In the face of all this, we cannot discern the truth in all its dimensions.Our research covers the following:1 - About his biography.2 - His candidacy for the mayoral elections of the Greater Istanbul.3- His victory in the elections in 1994